FREKUENSI GEN SIFAT KUALITATIF AYAM KAMPUNG - Dandi Hassan; Nibras Karnain Laya; Safriyanto Dako; Ari Ardiantoro (Jambura Journal of Animal Science, 2022)
The maintenance of free-range chickens in rural communities is done traditionally. Male chickens can be crossed with natural females, resulting in offspring that have various characteristics. The purpose of this study was to describe the performance of native chickens based on qualitative and quantitative characteristics in the Sangkub District, North Bolmong Regency. Data collection of 200 free-range chickens based on livestock density levels in several areas. Description analysis was used to describe the phenotype of native chickens. The results showed that the color of the feathers were colorless and the color of the feathers of Kampung chickens from Sangkub District were 8% and 92%, respectively. The combs found in male and female chickens were single, pea, ros and walnut at 71%, 21%, 6%, and 2%, respectively, while in free-range chickens they were 46% and 54%, respectively. The qualitative appearance of free-range chickens from Sangkup District has a more dominant coat color compared to white feathers. The single comb form is dominant in males and the pea comb is dominant in females. The color of the calf in the rooster is black, while the hen is white.